Application of voltammetric technique to the analysis of indanthrene dye in alkaline solution - Zanoni, Maria Valnice Boldrin [UNESP]; Sousa, W. R.; de Lima, J. P.; Carneiro, P. A.; Fogg, A. G. (Elsevier B.V., 2006)
The Indanthrene Olive Green B (C.I. Vat Green 3; C.I. 69500), VG3 dye, a vat dye bearing an anthraquinonoid group and a ketonic group, can be detected by differential pulse voltammetry in alkaline solution using glassy carbon electrode. on the adsorbed form the dyes are reduced into three cathodic steps at -0.54 V, -0.65 V and -0.93 V vs Ag/AgCl. The leuco form generated after previous electrolysis at controlled potential of -1 V can be detected by voltammetry due to its reoxidation peak at -0.08 V. An analytical method is proposed for determining the vat dye using modified glassy carbon electrode by electrochemical activation in alkaline medium. Linear relationship was observed between l(Pu) vs concentration from I X 10(-5) mol L-1 to 6.0 X 10(-4) mol L-1. The detection limit was calculated to be 9.3 X 10(-6) mol L-1. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: indanthrene dyes; voltammetric reduction; dye determination; vat dyes